Per Capita Health Expenditure at a Municipal Hospital: Perspective from a General Practice Hospital in Rural Nepal - Pawan Kumar Bajaj Agrawal; Baburam Giri; Priyanka Gupta; Anjan Nepali; Suraj Parajuli (Journal of Karnali Academy of Health Sciences, 2025)
Background: The Government of Nepal has been strengthening the primary care and fulfilling the commitment of universal health coverage by upgrading and establishing municipal hospitals. These hospitals are expected to be affordable and accessible. It is necessary to understand the health expenditure at these primary centers to reflect upon the productivity, especially in low income countries like Nepal struggling with adequate expenditure in health. Therefore, we aimed to reflect upon the temporal trend of per capita health expenditure in a rural municipal hospital.